2008
DOI: 10.1194/jlr.m700525-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and treatments that affect the lifespan of the NPC1 mouse

Abstract: Niemann-Pick type C (NPC) disease is a multisystem disorder caused primarily by a mutation in the npc1 gene. These studies evaluated the effect of genetic background, deletion of additional genes, and administration of several agents on the age at death in a murine model of this disorder. Such factors as differing strain background or genetic drift within a given background in the npc1 2/2 mouse significantly altered the age at death and the degree of organ disease. Genetic deletion of Siat9 (GM3 synthetase) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
137
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 20 publications
9
137
2
Order By: Relevance
“…This is consistent with its better ability to extract cholesterol from biologic membranes (13)(14)(15). This observation may be important because relatively high amounts of HPβCD need to be injected to obtain a partial therapeutic effect (8)(9)(10)(11)(12). Additionally, the observation that CD works from inside LE/LY suggests that modifications that target CDs for endocytic uptake and retention might significantly enhance its potency.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…This is consistent with its better ability to extract cholesterol from biologic membranes (13)(14)(15). This observation may be important because relatively high amounts of HPβCD need to be injected to obtain a partial therapeutic effect (8)(9)(10)(11)(12). Additionally, the observation that CD works from inside LE/LY suggests that modifications that target CDs for endocytic uptake and retention might significantly enhance its potency.…”
Section: Resultssupporting
confidence: 58%
“…All of the studies showing CD efficacy in murine models of NPC1 used HPβCD for treatment (8)(9)(10)(11). However, cell culture studies have shown that MβCD is more potent in extracting, delivering, and exchanging cholesterol than HPβCD (13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, both pharmacological chaperones (PCs) (i.e., small molecules such as cholesterol analogs that could bind and stabilize the fold) or a new class of compounds we refer to as proteostasis regulators (PRs) (19) that alter the cellular folding environment to ''repair'' the variant fold may favor repopulation of the LE with functional NPC1 and restoration of acceptor function. Strikingly, as proofof-principle of the key insights provided by Infante et al (13), cyclodextrins have recently been reported to correct NPC1 null mouse models of disease (20,21). Here, cholesterol binding activity of either internalized cyclodextrin or, possibly, the presence of an extracellular sink for cholesterol could supplement the shuttle activity of endogenous NPC2 to transfer cholesterol from internal membranes to favor efflux via ABCA1 or vesicular recycling pathways.…”
mentioning
confidence: 99%
“…Indeed, combination therapy of cholesterol mobilization with cyclodextrin-like cholesterol binding scaffolds (20,21) and a PC/PR (18) may prove to be synergistic to create a substantially improved trafficking and function environment as Kelly and colleagues (23) have demonstrated recently for Gaucher's disease.…”
mentioning
confidence: 99%